Strain localization in unsaturated elastic-plastic materials subjected to plane strain compression - Peric, Dunja; Zhao, Gaofeng; Khalili, Nasser (My University, 2014)
Analytical solutions have been derived for the onset of strain localization in a broad class of unsaturated elastic-plastic porous materials based on Bishop’s definition of effective stress. Critical hardening moduli for constant water content and drained loadings were found to be further gradual simplifications of the critical hardening modulus for an undrained loading. In addition, the solutions were found to reduce to the previously found solutions for fully saturated and monophasic porous materials by adequately adjusting bulk moduli of the pore fluids. This finding demonstrates that the mechanics of fully saturated and monophasic soils is the special simpler case of the mechanics of unsaturated soils. A diagnostic tool for detection of the inception of strain localization was developed by implementing the aforementioned solutions into a constitutive driver for a bounding surface plasticity model. The tool was used to further illustrate the strain localization behavior of unsaturated Bourke silt from the Bourke region of New South Wales, Australia, subjected to undrained, constant water content and drained loadings.
Keywords: Bifurcations; Elastoplasticity; Silts; Unsaturated soils